Activator Token KWh Meter Using Servo Motor SG90 Based on Arduino Uno Microcontroller - Mirda Khamidah; Sri Wahyu Suciyati; Humairoh Ratu Ayu; Gurum Ahmad Pauzi; Achmad Royhan (Journal of Energy, Material, and Instrumentation Technology, 2023)
The design of the kWh meter token activator using the SG90 Servo Motor based on the Arduino Uno microcontroller has been studied. The tools and materials used are the SG90 Servo Motor, PCA9685 Servo Motor Driver, Arduino Uno, 5V 1 A Adapter, pressure wire, and additional supporting tools. When pushing the kWh meter keypad, a servo motor at a 90° angle causes the wire to travel ideally perpendicularly. When the token value is entered into the interface, Arduino Uno executes the token value and tells the PCA9685 Servo Motor Driver to operate eleven SG90 Servo Motors to drive the push wire for the kWh meter keypad. The precision of the token number on the kWh meter and the display of the word "true" on the LCD kWh meter demonstrate the tool's effectiveness. The kWh meter Token Activator Tool successfully activated five new kWh meter Tokens with 100% correctness in terms of numbers, and each token took 44 seconds to activate. They are making an error and wasting time activating the kWh meter token.